2015
DOI: 10.1370/afm.1848
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Prevalence of Concordant and Discordant Conditions on the Quality of Diabetes Care in Family Practices in England

Abstract: PURPOSE The purpose of this study was to examine the association between the prevalence of both diabetes-concordant and diabetes-discordant conditions and the quality of diabetes care at the family practice level in England. We hypothesized that the prevalence of concordant (or discordant) conditions would be associated with better (or worse) quality of diabetes care. METHODSWe conducted a cross-sectional study using practice-level data (7,884 practices). We estimated the practice-level prevalence of diabetes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 25 publications
0
24
0
3
Order By: Relevance
“…How comorbidity, defined as the presence of cooccurring NCDs in an individual [4,5], impacts diagnosis, treatment, and control of NCDs is an emerging area of research inquiry and has important clinical implications as highlighted in the recent National Institute for Health and Care Excellence guidelines for treating patients suffering from multiple NCDs [6]. A small number of studies in high-income countries show mixed results on the implications of comorbidities on the management and control of single NCDs, such as hypertension or diabetes [7][8][9][10]. A study in the United States revealed that the proportion of persons with uncontrolled hypertension increased as the number of unrelated comorbid NCDs increased [9].…”
Section: Introductionmentioning
confidence: 99%
“…How comorbidity, defined as the presence of cooccurring NCDs in an individual [4,5], impacts diagnosis, treatment, and control of NCDs is an emerging area of research inquiry and has important clinical implications as highlighted in the recent National Institute for Health and Care Excellence guidelines for treating patients suffering from multiple NCDs [6]. A small number of studies in high-income countries show mixed results on the implications of comorbidities on the management and control of single NCDs, such as hypertension or diabetes [7][8][9][10]. A study in the United States revealed that the proportion of persons with uncontrolled hypertension increased as the number of unrelated comorbid NCDs increased [9].…”
Section: Introductionmentioning
confidence: 99%
“…9 A 1% higher prevalence of diabetes at the practice level was found in regression analyses to be associated with a 0.031 lower achievement score on the logit scale. As shown in table 1, the effect of differences in prevalence on the untransformed achievement score differs, depending on the anchor achievement rate selected.…”
Section: Back-transformationmentioning
confidence: 89%
“…[7][8][9] The framework is a financial incentive scheme introduced by the UK government in 2004, which rewards practices on the basis of their performance on more than 100 quality indicators related to the clinical management of chronic disease, practice organisation and, patient experience. 10 For the clinical indicators, which are regularly reviewed and could be withdrawn, 11 practices are assessed on the basis of the percentage of eligible patients for whom each target is met (eg, the percentage of patients with coronary heart disease who give a blood pressure recording of ≤150/90 mm Hg).…”
Section: Summary Boxmentioning
confidence: 99%
“…9,12 Such pairings are referred to as being within the same 'system' or 'domain', 6 and as being either concordant (ie diabetes and obesity, diabetes and chronic kidney disease) or discordant (ie diabetes and asthma, diabetes and depression). 13,14 Finally, the complexity is detailed in literature concerning patients' experiences [15][16][17] and the impact of multimorbidity on quality of life. 18…”
Section: Discussionmentioning
confidence: 99%